PERAN ARMADA PENJUALAN DALAM PEMASARAN - Eka Yudhyani (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2015)
Along with the development of Indonesia's economy is growing rapidly led to the dynamics of social and economic life becomes dynamic. Perekonomoian dynamic growth led to the emergence of various businesses - businesses that sustain the economy of the State. The emergence of various kinds of companies will require an efficient marketing campaign.Marketing campaign is an effort to convey a message or information to the public, especially the customers about the existence of a product or service. The development of science and technology communication has no doubt contributed to the development of promotional activities. There are four promotional strategies collected in the promotion mix, ie advertising (advertising), sales promotion (sales promotion), publicity (publicity), and personal selling (private sale).Personal selling is an ability in executing a job, task - a task or obligation that may provide remuneration to the seller. Personal selling is direct interaction with one or more prospective buyers to make a presentation, answer questions, and receive orders. Personal selling is the most cost effective tool in the further stages of the buying process, particularly in building preferences, beliefs, and actions of buyers.